PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA JASA PENGIRIMAN PAKET PADA J&T EXPRESS DP SUGIO LAMONGAN - Yustika Wahyu Ningrum; Jojok Dwiridotjahjono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research aims to know the influence of service quality on customer loyalty throughcustomer satisfaction on the users package delivery services on J&T Express DP SugioLamongan. This research uses quantitative method, Because in this study the data obtainedin the form of numbers and analyzed by using the Analysis of SEM-Partial Least Square(PLS). The type and source of data used in this research is primary data and secondarydata. The technique of data collection is done by distributing questionnaires AndDocumentation. The population used in this study is consumers who already use a courierservice J&T Express DP Sugio Lamongan Number 638 consumers in 2021. The sampleused in this study were 90 respondents. Drawing technique the Sample is taken usingprobability sampling. Data analysis used is to use the method of partial least square (PLS)due to perform testing against the established relationship between one or moreindependent variables with one or more dependent variables. The results showed thatservice quality has a positive and significant impact on customer loyalty. service quality hasa positive and significant impact on Customer Satisfaction. customer satisfaction has apositive and significant impact on customer loyalty. Indirectly the quality of service has apositive and significant impact on customer loyalty through customer satisfaction.